2022
DOI: 10.1111/ajps.12690
|View full text |Cite
|
Sign up to set email alerts
|

Winners’ Consent? Citizen Commitment to Democracy When Illiberal Candidates Win Elections

Abstract: Democracy is in decline worldwide, primarily because voters elect candidates harboring antidemocratic aspirations. Scholars argue that elections animate the democratic spirits of winners and deflate those of losers, but what about contests ending in the victory of authoritarian candidates? To answer this question, we consider the dynamics of commitment to democracy in Brazil's 2018 presidential campaign. Drawing on AmericasBarometer data and an original five‐wave panel survey, we confirm that Jair Bolsonaro's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 70 publications
2
15
0
2
Order By: Relevance
“…The argument is different from yet consistent with the classical accounts described above as well as extant explanations of why voters support undemocratic political leaders (e.g., Graham and Svolik 2020;Frederiksen 2022aFrederiksen , 2022bCarey et al 2020;Touchton et al 2020;Bartels 2020;Albertus and Grossman 2021;Ahlquist et al 2018;Svolik 2020;Luo and Przeworski 2019;Braley et al 2021;Carey et al 2019;Simonovits et al 2022;Cohen et al 2022). For example, Linz (1978, 72) observed that defection in presidential systems-which should not be equated but surely overlaps with two-party systems-is costly due to a 'winner-takes-all'-logic.…”
Section: Theoretical Argumentmentioning
confidence: 65%
“…The argument is different from yet consistent with the classical accounts described above as well as extant explanations of why voters support undemocratic political leaders (e.g., Graham and Svolik 2020;Frederiksen 2022aFrederiksen , 2022bCarey et al 2020;Touchton et al 2020;Bartels 2020;Albertus and Grossman 2021;Ahlquist et al 2018;Svolik 2020;Luo and Przeworski 2019;Braley et al 2021;Carey et al 2019;Simonovits et al 2022;Cohen et al 2022). For example, Linz (1978, 72) observed that defection in presidential systems-which should not be equated but surely overlaps with two-party systems-is costly due to a 'winner-takes-all'-logic.…”
Section: Theoretical Argumentmentioning
confidence: 65%
“…Empirically, it shows us that more parties are not better for democratic stability, when it comes to opposition to undemocratic politicians. The paper also contributes to the burgeoning literature explaining why voters support undemocratic political leaders (e.g., Graham and Svolik 2020;Frederiksen 2022a;Carey et al 2020;Touchton et al 2020;Bartels 2020;Albertus and Grossman 2021;Ahlquist et al 2018;Braley et al 2021;Simonovits et al 2022;Cohen et al 2022;Krishnarajan 2022). Whereas prior studies have typically focused on the characteristics of the options within the system-such as to which extent they are polarized-this paper sheds light on what happens when the very number of options in the party system increases or decreases.…”
Section: Introductionmentioning
confidence: 84%
“…The argument relates to the classical accounts on party systems and democratic stability (Sartori 1976;Dahl 1971;Lipset 1983;Linz 1978;Lijphart 1999;Anderson and Guillory 1997) as well as extant explanations of why voters support undemocratic political leaders (e.g., Graham and Svolik 2020;Frederiksen 2022aFrederiksen , 2022bCarey et al 2020;Touchton et al 2020;Bartels 2020;Albertus and Grossman 2021;Ahlquist et al 2018;Svolik 2020;Luo and Przeworski 2019;Braley et al 2021;Carey et al 2019;Simonovits et al 2022;Cohen et al 2022). Although not touching upon support for undemocratic politicians, Linz (1978, 72) observed that defection in presidential systems-which should not be equated but surely overlaps with two-party systems-is generally costly due to a 'winner-takes-all'-logic.…”
Section: Theoretical Argumentmentioning
confidence: 95%
“…These results chime with Mazepus and Toshkov (2022), who found that citizens who voted for a losing party in the previous elections are more supportive of checks and balances than those who supported a winning party. Similarly, evidence from Brazil indicates that opposition supporters retain their support for democratic governance even at times of democratic backsliding (Cohen et al 2021).…”
Section: Stage 1: Voters Evaluate (Un)democratic Elite Conductmentioning
confidence: 99%